Factors preventing the successful implementation of a Fall Prevention Programme (FPP) in an acute care hospital setting in Abu Dhabi, United Arab Emirates - Haripersad, Vasanthee (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MCur)--University of Stellenbosch, 2011.